Health Literacy Among Patients Undergoing Hemodialysis: A Descriptive Study - Jassem, Zahraa A.; Al-Ashour, Ibrahim A. (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The study aims to assess the level of health literacy among patients undergoing hemodialysis. Methods: A descriptive study using Convenience sampling was conducted among (171) patients undergoing hemodialysis in Al Najaf Al-Ashraf, from September 19th, 2022, to January 1st, 2023.Health literacy was measured using the European Health Literacy Questionnaire (HL-EU-Q47). The collected data were analyzed using SPSS 21.0 and Fisher’s exact test. Results: The results revealed that (60.8%) of participants had inadequate health literacy, the participants reported difficulty in understanding health literacy (health care, disease prevention and health promotion), (66.7%) of participants faced challenges in understanding and engaging in health promoting behaviors. Additionally, there was a statistically significant relationship between health literacy and the participants Level of education. Conclusions: Participants have inadequate health literacy and difficulties in assessing, understanding, judging, and using health information, which led to unfollowing dietary restrictions, adhering to complex medication regimens, and miss out dialysis sessions. Recommendation: Healthcare providers should consider tailoring patient education and communication strategies based on individual health literacy levels to support hemodialysis patients effectively.